1990
DOI: 10.3354/meps061001
|View full text |Cite
|
Sign up to set email alerts
|

Sea scallop larvae Placopecten magellanicus on Georges Bank: vertical distribution in relation to water column stratification and food

Abstract: Vertical distribution of sea scallop larvae was studied from pump samples in mixed, stratified, and frontal areas of Georges Bank. The extent of larval aggregation was positively related to the degree of water column stratification. In mixed areas larvae were distributed evenly over the 40 to 50 m water column, while in stratified waters larvae showed subsurface peaks in concentration above the pycnocline. Where the pycnocline was well developed, differences in the larval centre of mass (ZCM) were associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
2

Year Published

1993
1993
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 31 publications
0
43
2
Order By: Relevance
“…Approximately 540000 D-stage larvae were introduced into each replicate 9.5 m deep tube in the Tower Tank, giving a final larval concentration in each tube of -0.20 larvae ml-l. This concentration is somewhat lower than typical hatchery larval rearing densities of 1 to 5 larvae ml-l (Tremblay 1988), but at least 2 orders of magnitude greater than maximum densities found on Georges Bank [Tremblay & Sinclair (1990a) reported peaks in larval concentration within the water column as high as 0.002 larvae ml-'1. While experimental larval concentration was markedly greater than natural densities, it represents approximately the lowest concentration at which workable numbers of spat can be collected under such conditions.…”
Section: Methodsmentioning
confidence: 89%
See 1 more Smart Citation
“…Approximately 540000 D-stage larvae were introduced into each replicate 9.5 m deep tube in the Tower Tank, giving a final larval concentration in each tube of -0.20 larvae ml-l. This concentration is somewhat lower than typical hatchery larval rearing densities of 1 to 5 larvae ml-l (Tremblay 1988), but at least 2 orders of magnitude greater than maximum densities found on Georges Bank [Tremblay & Sinclair (1990a) reported peaks in larval concentration within the water column as high as 0.002 larvae ml-'1. While experimental larval concentration was markedly greater than natural densities, it represents approximately the lowest concentration at which workable numbers of spat can be collected under such conditions.…”
Section: Methodsmentioning
confidence: 89%
“…Aggregation of larvae of Placopecten magellanicus at or above thermoclines/pycnoclines has been documented both in the field (Tremblay & Sinclair 1988, 1990a and in, laboratory mesocosms (Gallager et al 1996, Manuel et al 199613). In a previous study, found that settlement of giant scallop larvae-spawned from adults collected from Newfoundland, Canada-in 9 m deep thermally stratified mesocosms (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Because the density structure of the water column was primarily a function of temperature, temperature accounted for most of the variation in larval abundance for most taxa. The presence of larvae in a particular water layer may be the result of changes in their buoyancy and changes in water density (Tremblay & Sinclair 1990. The role of buo yancy in the vertical distribution of gastropod larvae is not known.…”
Section: Patterns In Larval Vertical Distributionmentioning
confidence: 99%
“…Physical (thermoclines, haloclines, pycnoclines) or biological (food patches) discontinuities in the water column can affect larval vertical distribution (Tremblay & Sinclair 1990, Raby et al 1994, Metaxas & Young 1998, Sameoto & Metaxas 2008, Daigle & Metaxas 2011. Physical clines often restrict bivalve larvae to a particular layer (Tremblay & Sinclair 1990 due to changes in buoyancy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation